2017
DOI: 10.1007/978-1-4939-7407-8_17
|View full text |Cite
|
Sign up to set email alerts
|

3D Histomorphometric Reconstruction and Quantification of the Optic Nerve Head Connective Tissues

Abstract: Accurately characterizing the 3D geometry of the optic nerve head neural and connective tissues has been the goal of a large and important body of scientific work. In the present report, we summarize our methods for the high-resolution, digital, 3D histomorphometric reconstruction of the optic nerve head tissues, including their visualization, parameterization, and quantification. In addition, we present our methods for between-eye comparisons of this anatomy, and their use to determine animal-specific and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Our method for 3D HMRN, delineation (Figure 13) and parameterization (Figures 14–15) of the monkey ONH has been described within a series of previous reports (Burgoyne et al, 2004; Downs et al, 2007; Lockwood et al, 2015; Pazos et al, 2016; Reynaud et al, 2016; Yang et al, 2007a; Yang et al, 2009a; Yang et al, 2007b; Yang et al, 2011b) and is summarized in detail in a recent book chapter (Yang et al, Accepted for publication Nov 2016 Forthcoming 2017). After, sacrifice and 3D reconstruction of a 6 mm trephine that contains the ONH and pp-sclera, 40 radial digital section images (4.5° degrees apart) of the reconstruction are manually delineated (Figure 13) and global values for 19 standard 3D HMRN parameters (Figures 14–15) are quantified as previously described (Downs et al, 2007; Yang et al, 2007a; Yang et al, 2009a; Yang et al, 2007b; Yang et al, 2011b).…”
Section: 0 Experimental Evidence Of Onh Connective Tissue Deformatimentioning
confidence: 99%
“…Our method for 3D HMRN, delineation (Figure 13) and parameterization (Figures 14–15) of the monkey ONH has been described within a series of previous reports (Burgoyne et al, 2004; Downs et al, 2007; Lockwood et al, 2015; Pazos et al, 2016; Reynaud et al, 2016; Yang et al, 2007a; Yang et al, 2009a; Yang et al, 2007b; Yang et al, 2011b) and is summarized in detail in a recent book chapter (Yang et al, Accepted for publication Nov 2016 Forthcoming 2017). After, sacrifice and 3D reconstruction of a 6 mm trephine that contains the ONH and pp-sclera, 40 radial digital section images (4.5° degrees apart) of the reconstruction are manually delineated (Figure 13) and global values for 19 standard 3D HMRN parameters (Figures 14–15) are quantified as previously described (Downs et al, 2007; Yang et al, 2007a; Yang et al, 2009a; Yang et al, 2007b; Yang et al, 2011b).…”
Section: 0 Experimental Evidence Of Onh Connective Tissue Deformatimentioning
confidence: 99%
“… 6 , 7 A previous histomorphometric study in NHPs showed that beams and pores in the LC ( Figure ) remodeled differently by quadrant, depth, and from the center to periphery. 8 Although LC microstructure 9 and 3D histomorphometry 10 of healthy and early experimental glaucoma (EG) in postmortem specimens from NHPs have been reported, there is a knowledge gap on the 3D microstructure of LC in healthy live monkeys. Considering the postmortem changes in structure, such as elimination of blood pressure and the collapse of blood vessels typically occupying the LC beams, impairment to fluid balance and transportation, and tissue stiffening, in vivo analysis is imperative to determine the actual LC structure that is involved in disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For our glaucoma diagnosis application, the ONH can simply be thought of as a complex 3D structure that can be represented by a cloud of points, as has been routinely performed in 3D histomorphometric and finite element studies. 16 18 …”
Section: Introductionmentioning
confidence: 99%